Explaining Internalized Oppression Using the Film, Claudine - Booker, Teresa A (Radical Teacher, 2019)
This is a teaching note. Therefore, I did not include an abstract. However, if there were one, it would be this: Lester and Tina Pine’s 1974 film, Claudine, is a fictitious story depicting the dating life of Claudine, a 36-year old African American mother of six who had been married twice (and “almost twice”). This film can be used to explain internalized oppression and how it might manifest itself differently even in individuals from the same families